KOMUNIKASI INTERPERSONAL PIMPINAN DAN BAWAHAN DALAM MENINGKATKAN KINERJA PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN KAMPAR - Resti Herfinda; Nova Yohana (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Interpersonal communication is needed in activity in the world of work, so thatleaders and subordinates can better understand the performance of each employee.Interpersonal communication can be very effective and can also be very ineffective.Conflicts in such a relationship with a subordinate or subordinates leadership with asubordinate makes walking is not effective interpersonal communication. To foster andimprove interpersonal relationships need to improve communication quality by improvingrelations and cooperation between the various parties in the Department of Population andCivil Registration Kampar regency. This study aims to determine the openness, empathy,support, positive sense, and equality in interpersonal communication leaders andsubordinates in improving performance in the Department of Population and CivilRegistration Kampar regency.This research method is qualitative analysis of interpersonal communication thisstudy uses of Joseph A. Devito, which is part of the perspective humanistc. The location ofresearch at the Department of Population and Civil Registration Kampar regency. A.Rahman Saleh street Bangkinang City District of Kampar regency. Informants in this studyis the Head of Department and employees using purposive sampling technique. Datacollection techniques using observation, interviews and documentation.Results of research on interpersonal communication leaders and subordinates inimproving performance in the service population and civil registration Kampar district isseen from five aspects: openness, empathy, support, positive sense, and equality. Openness,transparency between leaders and subordinates are still lacking and the need forimprovement in terms of in-depth approach undertaken leadership. Empathy, empathygiven leadership to bawahnnya still less because only some employees who had had enoughconcerns to their leaders. Support, supportive attitude is not very effective leadershipwhere leaders only put pressure on subordinates that work quickly resolved. Positive sense,positive sense leader must be able to speak informally in the language of the heart to hissubordinates. Equality, equality leaders still being discriminating subordinates this createssocial jealousy among subordinates.Key word : Interpersonal communication, improving performance.